Insan Ilahiyah dalam perspektif Filsafat Transendental Mulla Sadra - Nano Warno; Nurul Ayn (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2021)
English Abstract Article deals to examine concept of human being in view of Mulla Sadra dan some of existensialtis philosopher through descriptive and analytic method along with hermeneutic approach to the main literature Islamic and the conclusion is that human beign in western is viewed in his existence and meanwhile in Islamic philosophy considered his soul and its faculty to embark in spiritual journeys